BURNOUT AND ITS IMPACT ON INDIVIDUALS - Firra Citra Ayu Rohimat (Study Program Guidance and Counseling, Univesitas Pendidik, 2021)
Adults have people prone to experience stress in which the course is located. At school, students experience stress because of the demands they face, such as assignments and exams. In the workplace, with the condition of stuffy, noisy, and the level of competition that is very high, employees early can feel the stress that suffocating. The term burnout is a new term in the world of work used to designate a type of anxiety. Burnout occurs due to factors related to the occupation (work-related factors) interacting with a jealous person's element and changing the physiological and psychological way, forcing someone to deviate from functioning normally. The article will explain the burnout phenomenon to create educational news about the burnout that often happened yet still lies in the environmental community. This study uses a literature study method. In the article is there is some influence of burnout and its impact.